Effect of Habitat Variability on Phenotypic Characters and Resource Allocation in Aralia cachemirica Decne. – An Endemic Medicinal Plant of Kashmir Himalaya: Effect of Habitat Variability on Phenotypic Characters and Resource Allocation in Aralia cachemirica Decne. – An Endemic Medicinal Plant of Kashmir Himalaya - Majid, Neelofar (International Journal of Pharmaceutical & Biological Archive, 2020)
The present study was carried out to determine the impact of habitat variability on morphological features and resource partitioning of the species under study. The species exhibited great variability in its morphological traits under different environmental conditions. The plants were more vigorous and taller at Ferozpur Nallah site followed by Kashmir University Botanical Garden while Aharbal population was shortest. During the present study, it was observed that partitioning of resources is not uniform among different parts of a plant, much resources were allocated toward the root followed by the shoot then by leaves, and least amount of resources was allocated toward inflorescence among the studied populations. Our results present a detailed account of the variation of phenotypic characters and changes in resource allocation patterns in relation to environmental conditions of this medicinal plant species